Bipolar Host Materials for Organic Light‐Emitting Diodes. Issue 1 (23rd November 2015) - Yook, Kyoung Soo; Lee, Jun Yeob
Abstract: It is important to balance holes and electrons in the emitting layer of organic light‐emitting diodes to maximize recombination efficiency and the accompanying external quantum efficiency. Therefore, the host materials of the emitting layer should transport both holes and electrons for the charge balance. From this perspective, bipolar hosts have been popular as the host materials of thermally activated delayed fluorescent devices and phosphorescent organic light‐emitting diodes. In this review, we have summarized recent developments of bipolar hosts and suggested perspectives of host materials for organic light‐emitting diodes. Abstract : Bipolar host materials have been widely used as the host materials for organic light‐emitting diodes to improve the quantum efficiency. In this work, recent progress in bipolar host materials and their application to OLEDs is reviewed.